(untitled) (Bangladesh Journal of Medical Science, 2017)
Objectives: Hypertension (HTN)/ high blood pressure (BP) is the most common cardiovascular condition affecting athletes. It is one of the critical challenges to care of a young athlete with high BP readings. For young competitive athletes, BP measurement should be performed during the pre-participation physical examination (PPE). BP has a significant influence of the physiological response to exercise. For child and adolescent athletes, an annual PPE is recommended by Sports medicine organizations. The aim of the study was to observe the patterns of present BP of the young sports persons of Dinajpur BKSP, Bangladesh. Materials and methods: This study was cross-sectional with convenient sampling technique and BP was measured by Auscultatory method. Results and Discussion: The results Showed no significant difference in diastolic BP among the young sports person of Dinajpur BKSP. A slight high systolic BP was observed only in one cricket student (130 mm Hg) which might be needed further investigation. Conclusion: Detecting high BP early will improve a childs health. Early diagnosis and treatment can reduce or prevent the harmful consequences of this disease. For young athletes, BP should be measured annually to maintain their resting heart rate in normal limit for fitness. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.439-442